Research on Welfare Robots: A Multifunctional Assistive Robot and Human–Machine System - Shuoyu Wang (Applied Sciences)
Welfare refers to the state of happiness and well-being experienced by a person. Welfare robots can directly contribute to people’s happiness and well-being. Specific welfare robots include health promotion robots, rehabilitation robots, assistive robots, nursing care robots, etc. Welfare robots are used in human living spaces and exert actions on humans through force and information. Because industrial robots that handle objects prioritize high speed and efficiency, if their control methods were to be applied directly to welfare robots, the results would be unsatisfactory and extremely dangerous. This paper proposes a method for constructing a human–machine system for welfare robots that includes the estimation of the user’s work intention, a measurement of riding comfort, and motion generation. Furthermore, various types of welfare equipment for people with walking disabilities have been developed, but most of them have a single function. Equipping small homes with many single-function devices is difficult, and their use is complicated and not standardized. Therefore, in this study, we developed a multifunctional assistive robot that integrates mobility, transfer, work support, and training. It is a typical welfare robot and is effective in preventing a user’s minor disabilities from becoming more severe. In this paper, we discuss the research challenge points of human–machine welfare robot systems and their current situation using the multifunctional assistive robot as a typical example.